Amplification and loss of dihydrofolate reductase genes in a Chinese hamster ovary cell line. - Kaufman, R J (1981)
During stepwise increases in the methotrexate concentration in culture medium, we selected Chinese hamster ovary cells that contained elevated dihydrofolate reductase levels which were proportional to the number of dihydrofolate reductase gene copies (i.e., gene amplification). We studied the dihydrofolate reductase levels in individual cells that underwent the initial steps of methotrexate resistance by using the fluorescence-activated cell sorter technique. Such cells constituted a heterogeneous population with differing dihydrofolate reductase levels, and they characteristically lost the elevated enzyme levels when they were grown in the absence of methotrexate. The progeny of individual cells with high enzyme levels behaved differently and could lose all or variable numbers of the amplified genes.